Odpowiedzi

2009-11-19T19:53:20+01:00
A) (x-9)(x-5)=x²+56-14x
xdo kwadratu-5x-9x+45=xdo kwadratu+56-14x
-14x+45=56-14x
0x=11

b) x²-(x+3)(x+4)=x+20
xdo kwadrau-[xdo kwadratu+4x+3x+12]=x+20
xdo kwadratu-xdo kwadratu-4x-3x-12=x+20
-7x-12=x+20
-6x=32/:(-6)
x=5i1/3

c) (x-1)(x+1)-x(x+2)-1=2(x+1)
xdo kwadratu-1-xdo kwadratu-2x-1=2x+2
-2x-2=2x+2
-4x=4/:(-4)
x=-1

d) 4(x+2)²=(2x+1)(2x+1)-2(2x-1)
4[xdo kwadratu+4x+4]=4xdo kwadratu+1-4x+2
4xdo kwadratu+16x+16=4xdo kwadratu+3-4x
16x+16=3-4x
20x=-13/20
x=-13/20

sorrki ze bez indeksu górnego w potegach....
2009-11-19T20:12:35+01:00
A) (x-9) (x-5) = x² + 56-14x
x²-5x-9x+45= x²+56-14x
x²-5x-9x-x²+14x= 56-45
0=11

b) x²- (x+3)(x+4) = x+20
x²-x²-4x-3x-12=x+20
x²-x²-4x-3x-x= 20+12
-8x =32 / ÷ (-8)
x=4

c) (x-1)(x+1)-x(x+2)-1=2(x+1)
x²+x-x-1-x²-2x-1=2x+2
x²+x-x-x²-2x-2x=2+1+1
-4x=4 /÷ (-4)
x=1

d) 4(x+2)²=(2x+1)(2x+1)-2(2x-1)
4(x²+4x+4)=4x²+1-4x+2
4x²+16x+16=4x²+1-4x+2
4x²+16-4x²+4x=1+2-16
20x= -13 /÷ 20
x= - 13/20